Necrostatin-1 Attenuates Trauma-Induced Mouse Osteoarthritis and IL-1β Induced Apoptosis via HMGB1/TLR4/SDF-1 in Primary Mouse Chondrocytes - Liang, Shuang; Lv, Zheng-tao; Zhang, Jia-ming; Wang, Yu-ting; Dong, Yong-hui; Wang, Zheng-gang; Chen, Kun; Cheng, Peng; Yang, Qing; Guo, Feng-jing; Lu, Wei-wei; Zhu, Wen-tao; et al. (Frontiers in Pharmacology, 2018)
Necrostatin-1 (Nec-1) is a specific small molecule inhibitor of receptor-interacting protein kinase 1 (RIPK1) that specifically inhibitinhibits phosphorylation of RIPK1. RIPK1 regulates inflammation and cell death by interacting with receptor-interacting serine/threonine protein kinases 3(RIPK3). We hypothesised that Nec-1 may have anti-inflammatory efficacy in patients with osteoarthritis (OA), as the pathophysiology of OA involves the activation of inflammation-related signalling pathways and apoptosis. In this study, we explored the effects of Nec-1 on interleukin (IL)-1β-induced inflammation in mouse chondrocytes and the destabilised medial meniscus (DMM) mouse model. Inhibiting RIPK1 with Nec-1 dramatically suppressed catabolism both in vivo and in vitro, but did not inhibit changes in subchondral bone. Nec-1 abolished the in vitro increases in matrix metalloproteinase and ADAM metallopeptidase with thrombospondin type 1 motif 5 (ADAMTs5) expression induced by IL-1β. However, adding high-mobility group box 1 (HMGB1) partially abrogated this effect, indicating the essential role of HMGB1 and Nec-1 in the protection of primary chondrocytes. Furthermore, Nec-1 decreased the expression of Toll-like receptor 4 (TLR4) and stromal cell-derived factor-1 (SDF-1), and attenuated the interaction between TLR4 and HMGB1. Western blot results suggested that Nec-1 significantly suppressed IL-1β-induced NF-𝜅B transcriptional activity, but not pathway. Micro-computed tomography, immunohistochemical staining, and Safranin O/Fast Green staining were used in vivo to assess the degree of destruction of OA cartilage, and the results were consistent with the in vitro experiments. Therefore, Nec-1 may be a novel therapeutic candidate to treat OA.